Association between socio-demographic factors and acceptance of family planning methods among scheduled caste women of Jorhat district, Assam - Medhi, Anuradha Hazarika; Saikia, Hiranya (International Journal Of Community Medicine And Public Health, 2023)
Background: In spite of the high knowledge, the rate of contraceptive methods use is not so satisfactory in India. The main objective of the health and family welfare programme is to reduce the knowledge, attitude and practice gap among the people of different societies, castes, religions and regions. The objective of the study is to find the association between socio-demographic factors and acceptance of family planning methods among the women belong to scheduled caste community which is one of the backward communities of India. Methods: A community based cross sectional study was conducted among scheduled caste community of Jorhat district, Assam. 612 married women of reproductive age group were selected using multistage sampling technique. Data were collected by personal interview using pretested, predesigned proforma. Chi-square test was used to see the association and all the analysis were done using SPSS- version 23. Results: 98.2% knew the family planning methods and 87.5% had positive attitude but only 65.3% practiced the methods. 58.3% women did not use the family planning methods because they want more children. The major source of information was mass media (76.8%) and majority of women (47.1%) used oral contraceptive pill (OCP) following by condom (21.6%). Most of the socio-demographic factors had significant association with the practice of family planning methods. Conclusions: There is a need to understand the various factors which influence the practice of family planning methods so that the it would help in designing effective family planning programme.